Approaches to Enhancing Electrical Conductivity of Pristine Metal–Organic Frameworks for Supercapacitor Applications. Issue 32 (17th July 2022) - Wang, Teng; Lei, Jiaqi; Wang, You; Pang, Le; Pan, Fuping; Chen, Kai‐Jie; Wang, Hongxia
Abstract: Metal–organic frameworks (MOFs), known as porous coordination polymers, have attracted intense interest as electrode materials for supercapacitors (SCs) owing to their advantageous features including high surface area, tunable porous structure, structural diversity, etc. However, the insulating nature of most MOFs has impeded their further electrochemical applications. A common solution for this issue is to transform pristine MOFs into more stable and conductive metal compounds/porous carbon materials through pyrolysis, which however losses the inherent merits of MOFs. To find a consummate solution, recently a surge of research devoted to improving the electrical conductivity of pristine MOFs for SCs has been carried out. In this review, the most related research work on pristine MOF‐based materials is reviewed and three effective strategies (chemical structure design of conductive MOFs (c‐MOFs), composite design, and binder‐free structure design) which can significantly increase their conductivity and consequently the electrochemical performance in SCs are proposed. The conductivity enhancement mechanism in each approach is well analyzed. The representative research works on using pristine MOFs for SCs are also critically discussed. It is hoped that the new insights can provide guidance for developing high‐performance electrode materials based on pristine MOFs with high conductivity for SCs in the future. Abstract : Three effective strategies (chemical structure design of conductive metal–organic frameworks (MOFs), composite design, and binder‐free structure design) are proposed to increase the conductivity and consequently the electrochemical performance of pristine MOFs in supercapacitors (SCs) through reviewing the works on pristine MOF‐based materials. The conductivity enhancement mechanism using pristine MOFs for SCs are also critically discussed.